PUBLIC SERVICE OF CREATIVE CITY IN PHUKET FROM THE PERSPECTIVE OF URBAN DEVELOPMENT (Journal of Governance and Development (JGD), 2022)
Public Service in Thailand is changed by national and international social factors which it can be said that an investment from privatesector in government affairs are one of the efficiency service opportunities to people. The public service of the creative city in Phuket according to the mission of the local government organization where the power and duty to solve problems in the area to meet theneeds of the people. The local government organizations carry out their missions in accordance with the National Economic and SocialDevelopment Plan provincial development plan district development plans, district development plans, public policies and policies of local administrators. Regarding to the seven (7) missions of local government organizations with Act Prescribing Plans and Decentralization Procedures for Local Government Organizations in 1999 which are comprise of: (1) Standard Structure; (2) Quality of life; (3) Social discipline and safety; (4) Investment plan and Commerce and tourism contribution; (5) Conservation management in natural resources and environment; (6) Religion, Culture, and Local innovation; and (7) Managing and supporting in missions of government agencies and local government organizations. In addition, the innovation of public service in the creative city of Phuket is to develop a city which can support the city growth. Therefore, the purpose of this paper is aimed to provide a brief overview of the public service innovation and creative city: Phuket, Thailand. This can serve as a lesson to the government in terms of formulating policies and strategies to handle the pandemic in the future.